Comparison of Bioethanol Production Efficiency from Aren Nira (Arenga pinnata Merr.) Using Tempe Yeast and Bread Yeast through Fermentation Process in Region X - Andi Apriany Fatmawaty (Agriculture Journal, 2025)
Bioethanol production from palm sap (Arenga pinnata Merr.) represents a promising renewable energy alternative due to the high sugar content that facilitates efficient fermentation. This study compares the efficiency of bioethanol production using tempe yeast (Rhizopus oligosporus) and baker’s yeast (Saccharomyces cerevisiae) at different concentrations during palm sap fermentation. Fermentation was conducted for five days, followed by distillation at 80–85 °C. Bioethanol yield and alcohol content were subsequently analyzed. The results indicate that tempe yeast produced a higher average bioethanol yield (45.59%) than baker’s yeast (41.40%), with corresponding alcohol contents of 16.20% and 14.13%. The optimal yeast concentrations were 2 g/200 mL for tempe yeast and 10 g/200 mL for baker’s yeast. Although the differences were not statistically significant, tempe yeast demonstrated more consistent fermentation performance. These findings suggest that tempe yeast is a promising alternative for enhancing bioethanol production from palm sap.